-13+19=-7c+19-6c

Simple and best practice solution for -13+19=-7c+19-6c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13+19=-7c+19-6c equation:



-13+19=-7c+19-6c
We move all terms to the left:
-13+19-(-7c+19-6c)=0
We add all the numbers together, and all the variables
-(-13c+19)-13+19=0
We add all the numbers together, and all the variables
-(-13c+19)+6=0
We get rid of parentheses
13c-19+6=0
We add all the numbers together, and all the variables
13c-13=0
We move all terms containing c to the left, all other terms to the right
13c=13
c=13/13
c=1

See similar equations:

| 2m-3-m=m+2-6 | | -6b-b=-7b+6 | | -6=(-11)+j | | -151=-8(-1+4n)+1 | | 9/7x+3=2/7x+11 | | y-(-10)=-41 | | Y+8=(x+14) | | -3(3+m)=9 | | 8-3m-m=5m-4-8m | | 5.8x=531.25 | | b-(-13)=5 | | -33=m+(-11) | | 1.6n=15 | | 273=209-w | | -16=8+s | | 14x+20-18+16=16 | | x+3/7x+2/7=6/5(x-5/7) | | 25=25-x | | -3+r=17 | | 0.2(10t-4)t=1.2 | | r+3/4=1/4 | | c-4=-1/2 | | 4.9x=248 | | x+3/7x2/7=6/5(x-5/7) | | x=2-6(4/9) | | 7=-4.9x^2+9.8x | | -w+5=163 | | 0=y2+0.9028y-0.1733 | | 9=2x+1-2 | | 20000=-19n+7n^2 | | 100/62.5=l/83 | | m=5/6(2,-9) |

Equations solver categories